On the role of access charges under network competition - Stefan Buehler; Armin Schmutzler (University of Zurich, Socioeconomic Institute, 2005)
We aim to clarify the role of access charges under two-way network competition, employing a reduced-form approach. Retaining the key features of specific network competition models but imposing less structure, we analyze the impact of changes in access charges on linear and non-linear retail prices. We derive sufficient conditions for usage fees to be increasing (and subscriber charges to be decreasing) in access charges. These conditions are shown to be satisfied only under rather restrictive assumptions on the demand for calls, suggesting that implementing collusion by inflating access charges is likely to be nonfeasible.
Keywords: D43; L43; 330; network competition; two-way access; collusion; nonlinear retail prices; Netzregulierung; Kartell; Unvollkommener Wettbewerb; Regulierung